Unveiling the genomic landscape of possible metastatic malignant transformation of teratoma secondary to cisplatin-chemotherapy: a Tempus gene analysis-based case report literature review - Farag, Christian M.; Johnston, Elena K.; Antar, Ryan M.; Issa, Shaher G.; Gadiwalla, Qasim; Tariq, Zoon; Kim, Sun A.; Whalen, Michael J. (Frontiers in Oncology, 2023)
In this case report, we describe a patient who developed metastatic liver cancer of unknown primary origin one year following the surgical removal of a retroperitoneal adenocarcinoma. The retroperitoneal adenocarcinoma is considered a malignant transformation of teratoma (MTT), given the patient’s distant history of testicular tumor excised 25 years prior and treated with chemotherapy. Despite no primary tumor being identified, the leading primary hypothesis is that the liver metastasis stemmed from the resected retroperitoneal adenocarcinoma from one year prior. We theorize that the patient’s cisplatin-based chemotherapy 25 years ago may have triggered the MTT, as documented in the existing literature. Using TEMPUS gene testing on both the retroperitoneal adenocarcinoma and the recently discovered liver metastasis, we identified several genes with variants of unknown significance (VUS) that could potentially be linked to cisplatin chemotherapy resistance. While we cannot conclude that this patient definitively underwent MTT, it remains the most plausible explanation. Future research should investigate both the validity of the genes we have uncovered with respect to cisplatin resistance, as well as other genes associated with cisplatin resistance to further understand the pathogenesis of cisplatin resistance for better prediction of treatment response. As the world of medicine shifts towards individualized therapies and precision medicine, reporting and analyzing genetic mutations derived from tumors remains imperative. Our case report aims to contribute to the growing database of defined mutations and underscores the immense potential of genetic analysis in directing personalized treatment options.